Rekontruksi Teori Partisipasi Politik Dalam Diskursus Pemikiran Politik Negara - Nur Rohim Yunus; Muhammad Sholeh; Ida Susilowati (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2017)
Abstract:Community involvement in a democratic party is important and must exist, because it is a manifestation of true democracy. Citizens are directly involved in the decision-making process, implementing decisions, influencing decision-making processes, influencing government policies, including relating to active involvement and passive involvement of each individual in the hierarchy of government political systems. All this involvement is known as a form of political participation. This study wants to rebuild political participation as a basic theory in the country's political thinking. So that the relationship can be drawn between the role of community political participation and the success of democracy itself.Keywords: Participation, Politics, Democracy Abstrak:Keterlibatan masyarakat dalam pesta demokrasi merupakan hal penting dan harus ada, karena ia merupakan perwujudan demokrasi yang sebenarnya. Warga negara terlibat langsung dalam proses pembuatan keputusan, melaksanakan keputusan, mempengaruhi proses pengambilan keputusan, mempengaruhi kebijakan pemerintah, termasuk berkaitan dengan keterlibatan aktif maupun keterlibatan pasif setiap individu dalam hierarki sistem politik pemerintahan. Semua keterlibatan ini dikenal sebagai bentuk partisipasi politik. Penelitian ini ingin membangun kembali partisipasi politik sebagai teori dasar dalam pemikiran politik negara. Sehingga dengannya dapat ditarik benang merah antara peran partisipasi politik masyarakat dengan kesuksesan demokrasi itu sendiri.Kata Kunci: Partisipasi, Politik, Demokrasi